PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI BELAJAR PADA MATA PELAJARAN EKONOMI MA MATHLAUL ANWAR - Muhammad Tafsil; Junaidi H. Matsum; Nuraini Asriati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was conducted with the intention of to find out the effect of reward and punishment to learning motivation on economic subjects in class X IPS at Senior High School Mathlaul Anwar Pontianak partially and simultaneously. This study uses multiple regression analysis with quantitative research forms. The sample in this study was 73 social studies class X students composed of three classes, namely a class of 27 students, class b of 23 students and class c of 23 students. Sampling uses random sampling technique. Data collection techniques used are indirect communication techniques using questionnaire instruments likert scale and documentary using documentation instruments. The results of processing data using the SPSS 20 application, can be known (1) There is a significant influence between the giving of rewards on learning motivation which is indicated by the significant value of 0.007 < 0.05; (2) There is a significant influence between giving punishment to learning motivation which is indicated by the significant value of 0.002 < 0.05; (3) There is a significant influence between the simultaneous reward and punishment of learning motivation which is indicated by the value of  = 6.56 >  = 3.13 with a significance value of 0.002.Keywords: Reward, Punishment, Learning Motivation